2009
DOI: 10.1097/mou.0b013e32831a7008
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser enucleation of the prostate and holmium laser ablation of the prostate: indications and outcome

Abstract: HoLEP represents a valid alternative to both transurethral resection of the prostate and open prostatectomy for treatment of patients suffering from lower urinary tract symptoms due to benign prostatic enlargement. The recently published long-term follow-up data demonstrate the durability of functional results. HoLEP can be offered as the size-independent gold standard treatment of patients with lower urinary tract symptoms because of benign prostatic enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 44 publications
1
25
0
1
Order By: Relevance
“…Despite the growing acceptance of transurethral procedures to treat large prostate glands 5,14,15 open simple prostatectomy has not lost its popularity. It is still first line treatment for a large prostate at many centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing acceptance of transurethral procedures to treat large prostate glands 5,14,15 open simple prostatectomy has not lost its popularity. It is still first line treatment for a large prostate at many centers.…”
Section: Discussionmentioning
confidence: 99%
“…It affects about 70% of men 70 years old or older and is a significant cause of morbidity in those with BPH greater than 60 gm. 1,2 Despite the increasing popularity of bipolar TURP and HoLEP, which some groups consider the best treatment for BPH regardless of prostate size, [3][4][5] open simple prostatectomy remains the procedure of choice for glands too large for safe endoscopic resection. 6 In recent years LSP was proposed.…”
mentioning
confidence: 99%
“…Slow ablation times and the development of more efficient tissue removal techniques such as HoLEP ultimately led to diminished utility of HoLAP for the treatment of BPH. However, with the introduction of high-powered, 100 W Ho:Yag laser systems, interest in HoLAP for the treatment of small to moderate-sized prostates has resurfaced because this technique is simpler to perform [6].…”
Section: Holmium Laser Ablation Of the Prostatementioning
confidence: 99%
“…11,12 Thus, we must improve the proficiency and reduce the learning curve of this technique. Our experience has shown that a basic grasp of the technique can be obtained after 30 TURP, 20 HoLEP and only 10 TmLRP-TT training cases.…”
Section: Teaching Mode and Learning Curvementioning
confidence: 99%